Exploring the in situ expression of vascular endothelial growth factor and endoglin in pemphigus foliaceus variants and pemphigus vulgaris. (6th April 2018) - Miyamoto, D.; Maruta, C.W.; Santi, C.G.; Zoroquiain, P.; Dias, A.B.T.; Mansure, J.J.; Burnier, M.N.; Aoki, V.
Abstract: Background: Erythroderma is a severe manifestation of pemphigus foliaceus (PF), a blistering disease mediated by IgG autoantibodies against desmoglein 1. Increasing evidence supports the contribution of angiogenic mediators in the pathogenesis of erythroderma. Objective: To evaluate the in situ expression of vascular endothelial growth factor (VEGF) and endoglin in patients with PF with erythroderma. Methods: Formalin‐fixed paraffin‐embedded skin samples obtained from patients with erythrodermic PF ( n = 19; 12 patients with endemic PF), non‐erythrodermic PF ( n = 17), pemphigus vulgaris (PV; n = 10), psoriasis ( n = 10) and healthy individuals (HI; n = 10) were processed in an automated immunohistochemistry platform utilizing anti‐VEGF and anti‐endoglin as primary antibodies. Reactivity was evaluated both manually (0 = negative; 1+ = mild; 2+ = intense) and through an automated microvessel analysis algorithm. Results: Vascular endothelial growth factor expression in erythrodermic PF was higher than in non‐erythrodermic PF ( P = 0.034) and in HI ( P = 0.004), and similar to psoriasis ( P = 0.667) and PV ( P = 0.667). In non‐erythrodermic PF, VEGF positivity was similar to HI ( P = 0.247), and lower than psoriasis ( P = 0.049) and PV ( P = 0.049). Both erythrodermic and non‐erythrodermic PF presented similar endoglin expression ( P = 0.700). In addition, endoglin positivity during erythrodermic PF was similar to psoriasis ( P = 0.133) and lower than PV ( P = 0.0009). Increased expression of in situ VEGF suggests that healing processes are triggered in response to tissue damage led by autoantibodies in PF, especially during erythroderma. Reduced endoglin positivity suggests that an unbalanced angiogenesis may occur during erythrodermic PF. Further studies may help to confirm if the regulation of VEGF and endoglin expression in patients with PF can contribute to control the healing process and enable disease remission. Conclusion: Overexpression of VEGF in erythrodermic PF as well as in PV and psoriasis points out a dysregulated repair process in severe forms of these diseases and suggests VEGF and endoglin could act as prognostic markers and future therapeutic targets to enable proper healing in PF.